Agreement between histopathological and intraoperative classifications for pediatric appendicitis and its relationship with the post-operative clinical outcome - Silva, Camila de Paula; Ortolan, Erika Veruska Paiva; Ribeiro, Sergio Marrone; Tedesco, Bruna Aliotto Nalin; Terra, Simone Antunes; Rodrigues, Maria Aparecida Marchesan; Lourenção, Pedro Luiz Toledo de Arruda (Frontiers in Pediatrics, 2022)
Introduction: some studies have shown poor agreement between intraoperative and histopathological classifications for appendicitis, despite their routine use in clinical practice. Objective: to investigate the agreement between histopathological and intraoperative classifications for pediatric appendicitis and evaluate the predictive potential of these classifications for the postoperative outcome. Methods: a retrospective, longitudinal, observational single-center study, carried out with 485 patients up to15 years of age, with a confirmed diagnosis of acute appendicitis by histopathological evaluation. The histopathological results classified the appendices as uncomplicated appendicitis when there was confirmation of the diagnosis of appendicitis without necrosis or perforation and complicated appendicitis when there was extensive necrotic tissue in the outer layer of the appendix or signs of perforation. The intraoperative findings were classified as uncomplicated appendicitis when the appendix presented with hyperemia and edema or fibrinous exudate and complicated appendicitis when the appendix showed necrosis and abscess or perforation. The kappa index determined the agreement and the prediction relationships using a generalized linear model. Results: 43.9% of cases were classified as complicated appendicitis by histopathological evaluation and 49.7% by intraoperative classification. The agreement analysis between the histopathological and intraoperative classification showed a Kappa index of 0.419 (0.337-0.501), considered a moderate agreement. There was an association (p<0.05) between the intraoperative classification and the postoperative clinical outcomes (time to start feeding, fever, intraabdominal collection, length of stay, the need for antibiotic therapy changing, need for ICU). There was no association between histopathological classification and postoperative outcomes. Conclusion: the agreement between the two classifications is moderate, and the intraoperative classification was able to predict the postoperative clinical outcomes.